E-074 Intravenous thrombolysis and endovascular therapy for acute ischemic stroke with internal carotid artery occlusion: a systematic review of clinical outcomes. (4th July 2012) - Mokin, M; Kass-Hout, T; Kass-Hout, O; Dumont, T; Kan, P; Snyder, K; Siddiqui, A; Levy, E
Abstract : Background and Purpose: Strokes secondary to acute internal carotid artery (ICA) occlusion are associated with extremely poor prognosis. Best treatment approach to acute stroke in this setting is unknown. We sought to determine clinical outcomes in patients with acute ischemic stroke due to ICA occlusion treated with intravenous (IV) systemic thrombolysis or intraarterial (IA) endovascular therapy. Methods: Using the PubMed database we searched for studies that included patients with acute ischemic stroke due to ICA occlusion who had received treatment with IV thrombolysis or IA endovascular interventions. Studies that provided data on functional outcomes beyond 30 days, mortality and symptomatic intracerebral hemorrhage (sICH) rates were included in our analysis. Results: We identified 28 studies with a total of 385 patients in the IV thrombolysis group and 584 patients in the endovascular group. Rates of favorable outcomes and sICH were significantly higher in the endovascular group than in the IV thrombolysis-only group (33.6% vs 24.9%, p=0.004 and 11.1% vs 4.9%, p=0.001, respectively). No significant difference in mortality rates was found between the two groups (27.3% in the IV thrombolysis group vs 32.0% in the endovascular group, p=0.12). Conclusions: According to our systematic review, endovascular treatment of acute ICA occlusion results in improved clinical outcomes. A higher rate of sICH following endovascular treatment does not result in an increased overall mortality rate. Randomized trials comparing systemic thrombolysis vs endovascular treatment are needed to determine the best treatment strategy in patients with acute ICA occlusion. Competing interests: M Mokin: None. T Kass-Hout: Genentech. O Kass-Hout: None. T Dumont: None. P Kan: None. K Snyder: Toshiba and ev3. A Siddiqui: NINDS 1R01NS064592-01A1, University at Buffalo. Shurtleff, Inc., Concentric Medical, ev3/Covidien Vascular Therapies, GuidePoint Global Consulting, Penumbra. Codman & Shurtleff, Inc, Genentech. Hotspur, Intratech Medical, StimSox, Valor Medical. Abbott Vascular, American Association of Neurological Surgeons, Neocure Group LLC, an Emergency Medicine Conference, Abbott Vascular. E Levy: Codman & Shurtleff, Inc., ev3/Covidien Vascular Therapies, Boston Scientific. TheraSyn Sensors, Inc. Medical Ltd., Mynx/Access Closure.